Wireless Sensor Network For Capsule Vehicle Application - Adam Hairi Azmi Noor Azmi (2023)
Nowadays, wireless sensor network has become an exciting new area of research in engineering. A lot of industries wish to develop and reform applications on realistic great scale sensor network. In this project, the efficiency and performance of capsule vehicle is the main objective to be monitored. The development of wireless sensor network could make the data and information collection simpler than ever. Besides, wireless sensor can be efficiently managed at system including sub-system level which allowing very low power consumption, high workability through software and adaptability by controlling new kind of sensors. With the three main variable to be analyze which are temperature, speed and current of the capsule vehicle, the information would be straightly send to the web server wirelessly. Thus, the power consumption of the vehicle will be examined. Next, the efficiency and performance would be monitor.